2022
DOI: 10.3389/fneur.2022.879764
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Nocturnal Blood Pressure Patterns and Other Influencing Factors With Lacunes and Enlarged Perivascular Spaces in Hypertensive Patients

Abstract: PurposeNocturnal blood pressure dipping patterns have been associated with an increased risk of Cerebral Small Vessel Disease (CSVD), which has not been well-studied. This study is aimed to explore the association of dipping patterns and other factors with lacunes and enlarged perivascular spaces (EPVS) in patients with hypertension.MethodsWe enrolled a total of 1,322 patients with essential hypertension in this study. Magnetic resonance imaging (MRI) scans and 24-h ambulatory blood pressure (BP) monitoring we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In the current investigation, the presence of PVS was very frequent in individuals with all levels of CV risk (including LR patients), and considering that more than 75% of them were hypertensive, this would support the effect of hypertension on the glymphatic system, expressed through the demonstration of enlarged PVS 29. Very recently Gao et al also reported the frequent occurrence of PVS in a very large cohort of individuals without neurological involvement 30…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the current investigation, the presence of PVS was very frequent in individuals with all levels of CV risk (including LR patients), and considering that more than 75% of them were hypertensive, this would support the effect of hypertension on the glymphatic system, expressed through the demonstration of enlarged PVS 29. Very recently Gao et al also reported the frequent occurrence of PVS in a very large cohort of individuals without neurological involvement 30…”
Section: Discussionsupporting
confidence: 75%
“…29 Very recently Gao et al also reported the frequent occurrence of PVS in a very large cohort of individuals without neurological involvement. 30 More severe WMH (Fazekas 2-3) were encountered in one third of the patients included in this investigation, being significantly more frequent and severe in the M/HR group. It is important to emphasise that these more severe WMH scores were also present in 14% of LR patients.…”
Section: Revised Chartsmentioning
confidence: 64%
“…The studies by Klarenbeek et al and Gao et al support this notion. 16 , 17 The significant correlation with lipoprotein a suggests a role for lipid metabolism abnormalities in the development of EPVS. This may relate to atherosclerosis and vascular inflammation, 18 , 19 known risk factors for cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%